Indigenization of Principal Officers of Tertiary Institutions in Nigeria: Implications and Way Forward - Niyi Jacob Ogunode; Aji Adimbo Agyo (International Journal on Integrated Education, 2022)
Recently, the Minister of Education, Adamu Adamu, confirmed at a National Assembly hearing in 2019 that he had been under pressure from indigenes of host communities insisting on producing the VCs of Federal Universities (Punch, 2022). The call by the host communities of the tertiary institution especially the Universities in Nigeria for their indigenous sons and daughters to be appointed as principal officers of the Federal and State tertiary institutions is a current problem facing University education in Nigeria. This paper examined the implications of the indigenization of principal officers or domestication of principal officers of the tertiary institution especially the Universities in Nigeria and suggested the way forward. Quantitative and quantitative data were used to provide empirical support to the various points raised in this paper. The paper concluded that poor international outlook, poor international rating, bad governance, under-development, discouragement of foreign academics, bad international image and less competition are the implications of the indigenization of principal officers or domestication of principal officers of the tertiary institution (Universities) in Nigeria. Based on this problem identified, the paper recommended that among other things, the Federal and State government should grant autonomy to all public Universities to allow Universities management to run the system based on merit and devoid of political influence.